Penerapan Konsep Storynomics Tourism Dinas Kominfo Surabaya Dalam Mempromosikan Pariwisata Kota Melalui Akun Instagram @Sapawargasby - Arvins Labibah Mahirah; Fitria Widiyani Roosinda; Ariyan Alfraita (CV. ITTC INDONESIA, 2026)
The development of digital technology has encouraged social media, particularly Instagram, to become a strategic platform for tourism promotion through visuals and narratives. Although Surabaya possesses significant potential in historical, cultural, and urban tourism, the city is often perceived as having limited tourist destinations due to promotional strategies that tend to be informative and lack emotional engagement. Therefore, the concept of Storynomics Tourism has been implemented by the Surabaya Communication and Informatics Office through the Instagram account @sapawargasby to present tourism promotion in the form of creative and meaningful storytelling. This study employs a descriptive qualitative method using content analysis, documentation, and. The findings indicate that a story-based approach is able to build emotional connections with the audience and strengthen the positive image of Surabaya’s tourism, thereby potentially changing public perceptions of the city as a diverse destination with historical value